The diversity of well-being indicators: a latent profile analysis - Horton, Calen J.; Walsh, Lisa C.; Rodriguez, Anthony; Kaufman, Victor A. (Frontiers in Psychology, 2024)
Research on the dimensional structure of subjective well-being (SWB) suggests a five-dimensional solution, consisting of the three established dimensions of life satisfaction, positive affect, and negative affect, and two additional empirically supported dimensions: domain satisfaction and happiness. While these dimensions can be aggregated into a superordinate SWB construct, little research has explored how these dimensions differ in their variation across subpopulations of individuals. The present study addresses this gap via secondary analysis of a sample of 1,487 partnered individuals, using the five dimensions of SWB as indicators for latent profile analysis. Analyses returned five profiles, which we labeled Satisfied, Ambivalent, Indifferent, Dissatisfied, and Very Dissatisfied. In the Ambivalent and Indifferent profiles, the dimensions of negative affect and happiness exhibit discrepant behavior, resulting in shape differences. The five profiles are organized with reference to the external criterion of couple satisfaction. At the theoretical level, the results of the present study have the potential to inform current debates about the structure of well-being. These findings suggest that, while SWB can usually be measured as a unidimensional construct, there is still merit to using multidimensional approaches and alternative forms of measurement-such as LPA-that capture complexities normally absent from unidimensional treatments. At the practical level, the results of the current study have the potential to inform well-being interventions (both clinical and otherwise), suggesting that those dealing with well-being in real life situations should pause before concluding that the absence of negativity implies the presence of positivity, or vice versa.